(untitled) (Research, Society and Development, 2024)
Introduction: Sport climbing, a challenging activity that involves climbing routes up to 50 meters high or blocks up to 6 meters high, has grown in popularity, especially after its inclusion as an Olympic sport in 2016. Objective: to investigate the prevalence and factors associated with eating disorders among climbers in the Federal District and Goiás. Methods: this is an observational cross-sectional study that involved the application of an online questionnaire, through Google Forms, with questions about eating habits, based on the Eating Attitudes Test-26 (EAT-26), a widely used instrument to assess eating behaviors related to eating disorders. The sample consisted of 135 adult participants of both sexes, selected by convenience among climbers of different experience levels and climbing styles. Results: Most participants expressed concerns about weight and eating, with 54.2% fearing gaining weight and 75.6% worried about food. Regarding nutritional status, 82.7% were eutrophic, and most believed that body weight impacts climbing performance (62.9%). Conclusion: The appreciation of climbing progress and the belief that nutrition directly impacts well-being suggests an awareness of the importance of physical and psychological factors in sports. These findings may guide future interventions aimed at balancing mental health, nutrition, and sports performance.